A Family Education in Providing Auditory Stimulus to Patients with Decreased Consciousness: Providing Auditory Stimulus - Erianti, Susi; Anggreny, Yecy; Syamputra, Muhammad Hafiz (Lembaga Dongan Dosen, 2025)
Decreased consciousness is a serious clinical condition that requires special treatment, especially in patients treated in intensive care units. One non-pharmacological approach that can be done by families to support the process of restoring patient consciousness is to provide auditory stimuli. Auditory stimuli, especially those originating from family voices such as name calls, conversational sounds, or prayer recordings, are believed to have a positive effect on patient neurological activation. Family involvement in providing this stimulus not only has the potential to increase the patient's conscious response, but also provides important emotional support during the patient's critical period. The results of education showed that there was an increase in family knowledge in providing auditory stimuli before (pre-test) which was 65% to 86% after (post-test), meaning that there was a difference in family knowledge after education was carried out. It is hoped that families will be directly involved in patient care in the intensive care room by providing auditory stimuli as one of the interventions to help restore patient consciousness